Історична пам'ять та наратив української національної ідентичності в історичній повісті Святомира-Михайла Фостуна «Нас розсудить Бог» - Марина Богданова (International Journal of Slavic Studies, 2022)
The article investigates the historical memory of the literary work written by Sviatomyr-Mykhailo Fostun “God will judge us”. The author chose the times of confrontation between the Cossack officers and representatives of the Collegium of Little Russia as the background for the action. Living in different European countries, the author had freedom to express his creative ideas. The narrative of national identity is expressed at all levels of the work. The author focuses on the formation of the national elite. Analyzing the defeats of Ukraine in the national liberation struggle, Sviatomyr-Mykhailo Fostun sees the future of independent Ukraine in the unity of experienced politicians of the older generation with educated Ukrainian youth and with the support of leading European politicians. We analyzed “places of memory” (P. Nora) in the book. They are associated with the topos of the cities Glukhov, Halle, Astrakhan, St. Petersburg and locus: the market squares, streets, villages and others. Each of them depicts a certain society, where confrontations take place on social, economic and political levels. In addition, they are a kind of markers that distinguish the society of each city. The city of Hlukhiv is marked by the struggle for the rights and freedom, the German city of Gelle is characterized by the freethinking and democracy of its inhabitants, and the Russian cities of Astrakhan and St. Petersburg appear as centers of tyranny and despotism. We investigated objects that go beyond the space of things. The Hetman's mace, which Polubotok takes in his hands in solitude, portraits of Hetmans of Ukraine in the cabinet, which seemed to witness the events, a Cossack saber with the coat of arms of Andriy Voynarovsky engraved on it; a picture of Cossack Mamai, who seemed to mock the representative of the Collegium of Little Russia, have a certain history, acquire a symbolic meaning for the Ukrainian nation.